Peranan Kepala Dusun Dalam Membantu Tugas Penghulu Di Kampung Belutu Kecamatan Kandis - Rahma, Novia; Rahman, Khairul (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
This study aims to determine how the role of the hamlet head in assisting the duties of the penghulu in kampung belutu, kandis sub-district. The theory in this study uses Pratina's theory (Salsabila, 2023: 28) there are four indicators in the role, namely authority, responsibility, clarity of purpose and scope of work. The method used is descriptive qualitative method. And the data collection techniques are through observation, interviews and documentation. With data analysis, namely data reduction, data presentation and conclusion drawing. Based on the analysis of four indicators, namely that the role of the hamlet head is not optimal and has not been implemented properly.